2022
DOI: 10.21203/rs.3.rs-2159503/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Integrative genomic analysis of childhood acute lymphoblastic leukaemia lacking a genetic biomarker in the UKALL2003 clinical trial.

Abstract: Incorporating genetics into risk-stratification for treatment of childhood B-progenitor acute lymphoblastic leukaemia (B-ALL) has contributed significantly to improved survival. In about 30% B-ALL (B-other-ALL) without well-established chromosomal changes, new genetic subtypes have recently emerged, yet their true prognostic relevance largely remains unclear. We integrated next generation sequencing (NGS): whole genome sequencing (WGS) (n = 157) and bespoke targeted NGS (t-NGS) (n = 175) (overlap n = 36), with… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Most studies have used target sequencing depths ranging from 60× to 90× to assess the diagnostic yield of WGS in hematological malignancies ( 15 , 19 , 20 , 60 ). In a study with an effective mean coverage of 50×, Duncavage and coworkers found that the sensitivity was 100% for the detection of CNVs and SVs but decreased to 84.6% for SNVs ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies have used target sequencing depths ranging from 60× to 90× to assess the diagnostic yield of WGS in hematological malignancies ( 15 , 19 , 20 , 60 ). In a study with an effective mean coverage of 50×, Duncavage and coworkers found that the sensitivity was 100% for the detection of CNVs and SVs but decreased to 84.6% for SNVs ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…Of note, restricted analysis of leukemic samples (L-only) could call primary genetic abnormalities in 37 out of 38 patients ( 20 ). A further study based on WGS investigated a subset of pediatric B-other ALL patients from the UKALL2003 trial and identified a subtype-defining lesion in 94% of the patients ( 15 ), whereas a similar study of 47 adult B-other ALL patients detected a class-defining aberration in 87% of patients ( 21 ).…”
Section: Introductionmentioning
confidence: 99%